Exercise as a promising alternative for sciatic nerve injury pain relief: a meta-analysis - Liu, Shunxin; Li, Qin; Wang, Huaiming; Zhang, Hongwei; Zhao, Qi; Su, Jinjun; Zou, Jiang; Feng, Pengjiu; Zhang, Aimin (Frontiers in Neurology, 2024)
Objective The efficacy of drug therapies in managing neuropathic pain is constrained by their limited effectiveness and potential for adverse effects. In contrast, exercise has emerged as a promising alternative for pain relief. In this study, we conducted a systematic evaluation of the therapeutic impact of exercise on neuropathic pain resulting from sciatic nerve injury in rodent models. Methods The PubMed, Embase, and Web of Science databases were retrieved before April 2024. A series of studies regarding the effect of treadmill, swimming, wheel and other exercises on neuropathic pain induced by sciatic nerve injury in rats and mice were collected. Using predefined inclusion criteria, two researchers independently performed literature screening, data extraction, and methodological quality assessment utilizing SYRCLE’s risk of bias tool for animal studies. Statistical analysis was conducted using RevMan 5.3 and STATA 12.0 analysis software. Results A total of 12 relevant academic sources were included in the analysis of controlled animal studies, with 133 rodents in the exercise group and 135 rodents in the sedentary group. The meta-analysis revealed that exercise was associated with a significant increase in paw withdrawal mechanical threshold [Standard Mean Difference1 (SMD) = 0.84, 95% confidence interval (CI): 0.28–1.40, p = 0.003] and paw withdrawal thermal latency (SMD = 1.54, 95%CI: 0.93–2.15, p < 0.0001) in rats and mice with sciatic nerve injury. Subgroup analyses were conducted to evaluate the impact of exercise duration on heterogeneity. The results showed that postoperative exercise duration ≤3 weeks could significantly elevate paw withdrawal mechanical threshold (SMD = 1.04, 95% CI: 0.62–1.46, p < 0.00001). Postoperative exercise duration ≤4 weeks could significantly improve paw withdrawal thermal latency (SMD = 1.93, 95% CI:1.19–2.67, p < 0.00001). Conclusion Exercise represents an effective method for improving mechanical and thermal hypersensitivity resulting from sciatic nerve injury in rodents. Factors such as pain models, the initiation of exercise, the type of exercise, and the species of rodent do not significantly impact the development of exercise-induced hypoalgesia. However, the duration of postoperative exercise plays a crucial role in the onset of exercise-induced hypoalgesia.